Hypocretins, sleep, and maternal behavior - Rivas, Mayda; Ferreira, Annabel; Torterolo, Pablo; Benedetto, Luciana (Frontiers in Behavioral Neuroscience, 2023)
The postpartum period is a demanding time during which mothers experience numerous physiological adaptations that enable them to care for their offspring while maintaining their well-being. Hypocretins, also known as orexins, are neuropeptides synthesized by hypothalamic neurons that play a fundamental role in several functions, including the promotion of wakefulness and motivated behaviors, such as maternal care. In this regard, several findings suggest that the activity of the hypocretinergic system increases in the early postpartum period and begins to decline as weaning approaches. In particular, hypocretins within the medial preoptic area, a crucial region during this period, modulate both maternal behavior and sleep. Although further studies are necessary to obtain a comprehensive understanding of the role of hypocretins in lactating females, current research suggests that this system participates in promoting active components of maternal behavior and regulating wakefulness and sleep adjustments during the postpartum period, potentially leading to increased wakefulness during this stage. These adaptive adjustments enable the mother to cope with the continuously changing demands of the pups.